Pendampingan Manajemen Administrasi Di Satuan Pendidikan Muadalah (SPM) Wustha Blokagung Banyuwangi - Hidayati, Nur; Nurkafidz Nizam Fahmi (IAI Darussalam, 2023)
Administrative management really needs to be understood, organized by grouping of the various tools used in the field of business, tasks, responsibilities and human resources in it, so as to be able to give coming out an organization that is in accordance with the vision and mission of the institution. In carrying out administrative management assistance at the Wustha Muadalah Education Unit (SPM), the service method or stages of implementing mentoring activities are used as follows: the first stage is the preparatory stage. The second stage is the program implementation phase. The third stage, namely the closing and review stage, carried out a thorough evaluation of the implementation of activities. The impact of the changes expected in this assistance are: a) The creation of an orderly administration. b) Complete and develop the Provider Performance Information System (SIKAP) application by adding a menu. c) Suggest an application for score and finance even though you already have the Education Management Information System (EMIS) application, minimum (a list of students' original grades before being transferred to an education report book or report card). d) Suggest all data stored in Google Drive.